Establishment of a platform based on dual RPA combined with CRISPR/Cas12a for the detection of Klebsiella pneumoniae and its KPC resistance gene - Tan, Meiying; Yi, Xueli; Liao, Chuan; Zhou, Zihan; Ren, Baoyan; Liang, Lina; Li, Xuebin; Wei, Guijiang (Frontiers in Bioengineering and Biotechnology, 2024)
Carbapenem resistant Klebsiella pneumoniae (CRKP) can cause serious hospitaland community-acquired infections. Treatment for CRKP infection is limited, resulting in prolonged hospitalization and high consultation costs. The KPC genotype has the highest detection rate of CRKP, and its mortality rate is higher than the overall mortality rate of CRKP. However, traditional testing methods have disadvantages such as long time and reliance on complex and sophisticated instruments, which are not conducive to rapid screening for CRKP. Therefore, this study aimed to establish a detection platform for early screening of CRKP so that effective antimicrobial therapy could be administered promptly to prevent the widespread spread of CRKP. We integrated dual RPA with CRISPR/Cas12a to establish a dual platform for the detection of Klebsiella pneumoniae (Kp) rcsA-specific gene and KPC resistance gene.Four result reading methods were established, including fluorescence detection (FD), blue light irradiation detection (BLID), ultraviolet irradiation detection (UID), and lateral flow test strips (LFTS). For the rcsA gene, the LOD of FD was 1×10 0 pg/μL, and the other three methods could detect 1×10 1 pg/μL of bacterial DNA. As for the KPC gene, four resultant readout methods were able to detect 1×10 2 pg/μL of bacterial DNA. In 59 clinical strains tested, the dual RPA-CRISPR/Cas12a detection of the rcsA had 100% sensitivity, specificity, and accuracy compared to the culture method.Compared with the drug sensitivity test, the sensitivity of dual RPA-CRISPR/Cas12a detection for the KPC was 85.71%, the specificity was 100%, and the accuracy was 94.92%. In summary, our dual RPA-CRISPR/Cas12a platform proved to be rapid, precise, and convenient for the efficient detection of Kp with KPC in the laboratory or at the point of care.